2018
DOI: 10.1186/s12885-018-4148-5
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions contribute to anchorage-independent clustering of breast cancer cells

Abstract: BackgroundCancer cell aggregation is a key process involved in the formation of clusters of circulating tumor cells. We previously reported that cell-cell adhesion proteins, such as E-cadherin, and desmosomal proteins are involved in cell aggregation to form clusters independently of cell migration or matrix adhesion. Here, we investigated the involvement of gap junction intercellular communication (GJIC) during anchorage-independent clustering of MCF7 breast adenocarcinoma cells.MethodsWe used live cell image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
(30 reference statements)
5
23
0
Order By: Relevance
“…We showed that during anchorage-dependent clustering, MCF-7 cells form large and dynamic actin-dependent protrusions, and that alteration of their formation by using actin-targeting drugs alters cluster formation in PDMS micro-wells. This result is consistent with our previous findings showing that latrunculin A affects cell aggregation in ultra-low attachment plates [16]. Given the fact that our experiments were performed using ultra low attachment plates on which cells could not adhere, the modifications of cell shape during the clusters formation could not be attributed to adherence to the substratum and migration.…”
Section: Comparisonsupporting
confidence: 93%
See 1 more Smart Citation
“…We showed that during anchorage-dependent clustering, MCF-7 cells form large and dynamic actin-dependent protrusions, and that alteration of their formation by using actin-targeting drugs alters cluster formation in PDMS micro-wells. This result is consistent with our previous findings showing that latrunculin A affects cell aggregation in ultra-low attachment plates [16]. Given the fact that our experiments were performed using ultra low attachment plates on which cells could not adhere, the modifications of cell shape during the clusters formation could not be attributed to adherence to the substratum and migration.…”
Section: Comparisonsupporting
confidence: 93%
“…Paclitaxel and vinorelbine are two microtubule targeting anticancer drugs that induce cell cycle block at mitosis and inhibition of cell proliferation [20]. To assess their effect on MCF-7 cell ability to compact and form clusters, cells treated with paclitaxel or vinorelbine for 24 hours were subjected to a previously described aggregation assay in which the progressive aggregation and compaction of 500 cells seeded in non-adherent 96-well plates are monitored by video-microscopy for 5 hours [15,16]. Cells treated with 100 nM paclitaxel or 20 nM vinorelbine for 24 hours accumulated in mitosis with very limited cell death, as confirmed by flow cytometry analysis (data not shown).…”
Section: Mcf-7 Cells Treated With Paclitaxel or Vinorelbine Less Effimentioning
confidence: 99%
“…4 Gap junctions (GJs) are specific cell-to-cell channels and have an essential role in intercellular communication, adhesion, and cell proliferation by allowing direct exchange of small molecules (<1 kD) and subsequently biologic signaling between adjacent cells. 5,6 Among GJ family members, gap junction alpha-1 protein (GJA1, Connexin43) is the predominant one expressed in epithelial tissues. It has been shown that down-regulation of GJA1 can result in aggressive growth of breast and lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that down-regulation of GJA1 can result in aggressive growth of breast and lung cancer. [5][6][7] In contrast, forced expression of GJA1 in various tumor cells can restore normal cell phenotypes and well differentiation. 8 These findings indicated a possible role of GJA1 as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer cell clustering has been reported to have a significant effect on the metastatic potential of the tumor . Specifically, Aceto et al reported that CTC clusters, although rare to find in blood flow, have a 23‐fold to 50‐fold increased likelihood of resulting in metastasis .…”
Section: Discussionmentioning
confidence: 99%